2018
DOI: 10.3390/catal8040138
|View full text |Cite
|
Sign up to set email alerts
|

Efficiently Enhancing Electrocatalytic Activity of α-MnO2 Nanorods/N-Doped Ketjenblack Carbon for Oxygen Reduction Reaction and Oxygen Evolution Reaction Using Facile Regulated Hydrothermal Treatment

Abstract: Scalable, low-cost and highly efficient catalysis of oxygen electrocatalytic reactions (ORR/OER) are required for the rapid development of clean and renewable energy conversion/storage technologies. Herein, two types of α-MnO 2 nanorods were prepared under hydrothermal treatment at 150 • C for 0.5 h (MnO 2 -150-0.5) or 120 • C for 12 h (MnO 2 -120-12), then supported on N-doped ketjenblack carbon (N-KB) as bi-functional ORR/OER catalysts. Their electrocatalytic activities toward ORR and OER were investigated s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 84 publications
(33 citation statements)
references
References 42 publications
(52 reference statements)
6
21
0
Order By: Relevance
“…Furthermore, the figures also suggest that the incorporation of α-MnO 2 in the activated carbon improved the ORR performance. This is observed also when doped carbon materials were added to the active electrocatalyst in other studies [10,15,18]. Among the samples that were analyzed, hydrochar and activated carbon produced from HTC at 250 • C for 12 h showed the highest performance, which is consistent with the CV results.…”
Section: Orr Activitysupporting
confidence: 85%
See 1 more Smart Citation
“…Furthermore, the figures also suggest that the incorporation of α-MnO 2 in the activated carbon improved the ORR performance. This is observed also when doped carbon materials were added to the active electrocatalyst in other studies [10,15,18]. Among the samples that were analyzed, hydrochar and activated carbon produced from HTC at 250 • C for 12 h showed the highest performance, which is consistent with the CV results.…”
Section: Orr Activitysupporting
confidence: 85%
“…On the other hand, it can be concluded that RHAC-and SDAC-supported α-MnO 2 exhibits ORR that proceeds both in 2-e − and 4-e − pathways, which resulted in an electron transfer number approaching three (3). In other studies [10,19,58], the electron pathway is influenced both by the individual ORR mechanism of the carbon support and the electrocatalyst. For such materials, ORR proceeds both in the composites, hence a mixed behavior can be expected.…”
Section: Orr Activitymentioning
confidence: 90%
“…Scheme 1. The reaction mechanism of UA.In the past few years, transition metals and metal oxides have received increasing attention in many fields, such as sensors and electrocatalysis, due to their unique sensing performance and superior electrocatalytic activity [9,11,23,24]. Among these metal oxides, cuprous oxide (Cu2O) is a new type of p-type semiconductor with a narrow band gap, which can also be easily excited by visible light.…”
mentioning
confidence: 99%
“…All DNA sensors were immersed into an electrochemical cell in 0.05 M Tris-HCl buffer solution (pH 7.40) containing 0.005 M [Fe(CN) 6 ] 3−/4− and 0.20 M KCl. Electrochemical impedance electrochemical impedance spectroscopy (EIS) is a nondestructive technique, which has been widely used in the biopotential sensors [ 39 ], electrocatalysis [ 40 , 41 ] and electrochemical sensors [ 31 ]. Herein, EIS was employed for the detection of target DNA.…”
Section: Methodsmentioning
confidence: 99%